Self-Healing Therapy for Body-focused Social Anxiety and Body Management in Adolescent Females with Body Image Concerns - Fatemeh Masoudizadeh; Fariba Hafezi; Sahar Safarzadeh; Zahra Dasht Bozorgi (Caspian Journal of Health Research)
Background: Body image concerns and social anxiety, often intertwined, can be significant challenges faced by many adolescent girls and may also serve as symptoms of underlying mental health conditions such as depression or anxiety disorders Objectives: The purpose of this study was to investigate the effectiveness of self-healing therapy on body-focused social anxiety and body management in adolescent girls with body image concerns. Materials & Methods: A quasi-experimental pre-test-post-test control group design was employed. The study population consisted of all female high school students with body image concerns in Ahvaz in 2023. Thirty female adolescents were randomly selected using a multi-stage cluster sampling method and assigned to two groups: An experimental group (n=15) and a control group (n=15). Data was collected using the body-focused social anxiety scale and body management scale. Self-healing therapy sessions were conducted with the experimental group over 12 sessions of 90 minutes each, while the control group received no intervention. Data was analyzed using analysis of covariance. Results: Self-healing therapy was found to be effective in significantly reducing body-focused social anxiety and improving body management in adolescent girls with body image concerns (P<0.001). Conclusion: Self-healing therapy has been shown to effectively reduce body-focused social anxiety and improve body management in adolescent girls struggling with body image issues. The study’s results highlighted the potential of this therapeutic approach as a promising intervention for this vulnerable population.